Survival dynamics in Portugal, a regional perspective - Nunes, Alcina (2011)
We address the post-entry performance of Portuguese firms for the seven NUT II regions in Portugal, by investigating the structural characteristics of survival, using both nonparametric methods and semi-parametric methods, during the period 1985-2007. In order to approach the prevalence of some stylized facts and determinants of new firm survival, a new entrepreneurship database was produced, using the administrative data of Quadros de Pessoal, following the Eurostat/OECD´s “Manual of Business Demography Statistics”. In the non parametric estimation, we use Kaplan-Meier survival functions and the Nelson-Aalen hazard rates. The semi-parametric estimation relates the survival capacity with seven explanatory variables and sector and year dummies. The main contribution of this work is the application of a recent internationally comparable methodology for entrepreneurship to provide a regional overview of firm and survival dynamics for all NUT II regions, over an extended period of time, while guaranteeing regional, national and international comparability. To our knowledge, there is not such a study that contemplates all this aspects and grants international comparability, over such a long time frame, made for any country.